2010
DOI: 10.1017/s0022112010001382
|View full text |Cite
|
Sign up to set email alerts
|

Drag and lift forces on a spherical particle moving on a wall in a shear flow at finite Re

Abstract: Recent research (Zeng, PhD thesis, 2007; Zeng et al., Phys. Fluids, vol. 21, 2009, art. no. 033302) has shown that both the shear-and wall-induced lift contributions on a particle sharply increase as the gap between the wall and the particle is decreased. Explicit expressions that are valid over a range of finite Re were obtained for the drag and lift forces in the limiting cases of a stationary particle in wall-bounded linear flow and of a particle translating parallel to a wall in a quiescent ambient. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 27 publications
6
75
0
Order By: Relevance
“…The results of our simulation are in a good agreement with results presented in [3,4] for Newtonian fluids. When the particle translational velocity Vp is low, the drag force coefficient Cd in non-Newtonian fluid is lower than in Newtonian one (Fig.…”
Section: Perfect Rollingsupporting
confidence: 89%
See 3 more Smart Citations
“…The results of our simulation are in a good agreement with results presented in [3,4] for Newtonian fluids. When the particle translational velocity Vp is low, the drag force coefficient Cd in non-Newtonian fluid is lower than in Newtonian one (Fig.…”
Section: Perfect Rollingsupporting
confidence: 89%
“…The distance between a sphere and the boundaries of the simulation volume was equal to 25 sphere diameters. To avoid numerical issues, a small gap d/200 between the sphere and the wall was presumed [2,3].…”
Section: Problem Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Haider and Levenspiel proposed equations for the drag coefficient of spherical and nonspherical particles [9], and numerical simulations have been conducted to investigate the drag forces acting on a nonspherical particle [10] [11]. Lee and Balachandar estimated drag forces on a translating and rotating particle in a wall-bounded linear shear flow [12], and drag forces on a particle with a uniform outflow from the surface were studied by Kurose et al [13]. Furthermore, Katoshevski et al experimen-tally investigated the relation between particle temperature and drag forces; the results showed that the drag force acting on a heated particle increased due to free convection around the particle [14].…”
mentioning
confidence: 99%